Development of virtual Herbarium in higher plants - Mohamed Fatimah, Mohd Noor Nor Nafizah, Alimon Hasimah, Abdul Aziz Nor Azah, Said Che Soh, (Universiti Pendidikan Sultan Idris, 2012)
Development of virtual Herbarium in higher plants by Mohamed Fatimah, Mohd Noor Nor Nafizah, Alimon Hasimah, Abdul Aziz Nor Azah, Said Che Soh,